Arctic Ocean, expedition crew members and flying boat - Ellsworth, Lincoln, 1880-1951 (1925)
"No. 21 Amundsen-Ellsworth 1925 Exped. Our only implements - 3 wooden shovels, a 2-lb pocket safety-ax and an ice anchor" Caption taken from Ellsworth, L., & National Americana Society. (1929). Air Pioneering in the Arctic: the Two Polar Flights of Roald Amundsen and Lincoln Ellsworth (pp. 57, No.21). New York: National Americana Society. Amundsen Ellsworth 1925 Expedition